Perbedaan Kesukaan, Kualitas Fisik, Kadar Protein Dan Kadar Air Kue Putu Ayu Substitusi Tepung Talas - Hutami, Safrinita Tri; Wahyuningsih (Jurnal Sains Boga, 2025)
Putu ayu cake is a traditional Indonesian snack. Consumption of wheat flour, the main ingredient, is still dependent on imports, necessitating the need for alternative local ingredients. Taro flour contains high levels of carbohydrates, fiber, and some protein, making it a potential substitute. The purpose of this study was to determine the effect of taro flour substitution on the level of preference, physical quality (texture and color), protein content, and moisture content of putu ayu cake. This study used a Completely Randomized Design (CRD) experimental method with four taro flour substitution treatments: 0%, 25%, 50%, and 75%, each replicated twice. The results showed that taro flour substitution affected the physical quality, color, and texture, but did not significantly affect panelists' preference for all sensory attributes. The highest average preference score was found in the 25% taro flour treatment, with an overall score of 5.85. Protein content increased with increasing proportion of taro flour, with the highest result at 75% substitution at 7.25%. In contrast, air levels did not show a consistent pattern of increase or decrease between treatments.